2008
DOI: 10.1016/j.ejvs.2008.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Infective Abdominal Aortic Aneurysm due to Haemophilus Influenza Identified via the Polymerase Chain Reaction

Abstract: Infective abdominal aortic aneurysms due to Haemophilus influenza are rarely reported. We report a case in a 65 year old female presenting with abdominal pain, weight loss, pyrexia and elevated inflammatory markers. The patient was found to have an abdominal aortic aneurysm clinically and on CT scanning. At surgery, an inflammatory aneurysm was successfully repaired using an autogenous vein panel-graft. Tissue samples were analysed using the polymerase chain reaction, identifying H. influenza as the causative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 4 publications
(1 reference statement)
0
9
0
Order By: Relevance
“…5,6 Generally, Salmonella and staphylococcal species are the most common agent for infective aneurysm. [5][6][7] In this case, against expectation, H. influenzae was detected. H. influenzae is a rarely reported causative agent, with a limited number of isolated case report.…”
Section: The Contiguous Direct Spread Of Infection To the Arterialmentioning
confidence: 77%
“…5,6 Generally, Salmonella and staphylococcal species are the most common agent for infective aneurysm. [5][6][7] In this case, against expectation, H. influenzae was detected. H. influenzae is a rarely reported causative agent, with a limited number of isolated case report.…”
Section: The Contiguous Direct Spread Of Infection To the Arterialmentioning
confidence: 77%
“…The most common organisms identified in mycotic aneurysms are Salmonella spp., Mycobacterium tuberculosis , gram‐positive cocci, and gram‐negative bacilli, excluding Salmonella. 2 H. influenzae is a rarely reported causative agent, with a limited number of isolated case reports 3‐5 . All reported cases have been limited to the abdominal aorta and the cause of infection was associated with upper respiratory tract infection, cellulitis, or gastroenteritis.…”
Section: Discussionmentioning
confidence: 99%
“…If there is active infection, resection of the aorta and extra‐anatomic bypass or homograft replacement is the appropriate procedure. In all reported cases involving H. influenzae , in situ reconstruction with a prosthetic graft or autogenous vein graft was used, without the use of omental or muscle flaps 3‐5 . Müller et al demonstrated that in situ reconstruction with a prosthetic graft and rigorous debridement of all infected tissue was necessary and an omental pedicle was used when technically possible 6 …”
Section: Discussionmentioning
confidence: 99%
“…Other organisms occasionally isolated from mycotic aneurysms include Streptococcus species and Enterococcus species, Mycobacterium tuberculosis, Clostridium species (Moneta et al, 1998) and some Gram-negative bacilli. H. influenzae has been rarely implicated in this infection, with only a handful of case reports in recent years (Moneta et al, 1998;Whitfield et al, 2008), and only one other case involving H. influenzae type f (Adlakha et al, 1994) to our knowledge.…”
Section: Discussionmentioning
confidence: 99%